Being Edward James Olmos: Culture Clash and the Portrayal of Chicano Masculinity - Nohemy Solózano-Thompson (Studies in 20th & 21st Century Literature, 2008)
This paper analyzes how Culture Clash problematizes Chicano masculinity through the manipulation of two iconic Chicano characters originally popularized by two films starring Edward James Olmos - the pachuco from Luis Valdez’s Zoot Suit (1981) and the portrayal of real-life math teacher Jaime Escalante in Stand and Deliver (1988). In “Stand and Deliver Pizza” (from A Bowl of Beings, 1992), Culture Clash tries to introduce new Chicano characters that can be read as masculine, and who at the same time, display alternative behaviors and characteristics, including homosexual desire. The three characters in “Stand and Deliver Pizza” represent stock icons of Chicano masculinity. In the skit, these icons are forced to interact with each other and through this process become more complex and accessible representatives of Chicano masculinity. They are able to communicate with each other to create something tangible. The pizza of course is a comedic metaphor for contemporary American society—the new melting pot.
Keywords: chicano; Edward James Olmos; masculinity; pachuco; Luis Valdez; Zoot Suit; Jaime Escalante; Stand and Deliver; Culture Clash; melting pot; America; Mexican-American culture